TAFSIR SOSIAL-EKONOMIS DARI AJARAN KEPEMIMPINAN YESUS DALAM MATIUS 20:25-28: IMPLIKASINYA BAGI PELAYANAN GEREJA - Delvia Banni’; Frans Sanda, Seni Lolo, Esron, Santice Tiku (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This research adopts a literature review approach to delve into the teachings of Jesus' leadership as revealed in Matthew 20:25-28. The primary focus of the study is to understand the socio-economic context during Jesus' time and how these teachings critique and influence power structures and leadership at that time. Through the analysis of the biblical text and examination of historical exegesis, this research reveals that Jesus' leadership teachings offer a new paradigm that invites Christians to explore the social and economic dimensions within the context of church ministry. In Matthew 20:25-28, Jesus emphasizes the importance of selfless service, overturning hierarchical norms, and urging disciples to be servants to one another. A deeper understanding of the social and economic context during Jesus' time provides insights into the implications of these teachings for church ministry in the contemporary era. This study offers insights into how the principles of Jesus' leadership teachings can shape and renew leadership structures within the church, advocating for the integration of inclusive service that is attentive to the socio-economic needs of the community. The research provides examples of applying these concepts in the context of church ministry and identifies potential challenges and conflicts that may arise. The findings of this research make a significant contribution to the discourse on the theology of leadership and church ministry in modern society.